Efektifitas Aplikasi E-Posyandu Kesehatan (ePoK) terhadap Partisipasi Orang Tua dalam Stimulasi Pertumbuhan dan Perkembangan Balita - Melly damayanti; Rita Ridayani; Vina Jayanti; Fauziah Yulfitria (Universitas Faletehan, 2025)
Parents play a crucial role in child growth and development due to high-intensity interactions since birth. Parental participation is critical to child health, requiring them to possess information and skills for early detection and providing growth stimulation. This study aims to examine the effectiveness of E-Posyandu Health application in increasing parental participation in stimulating the growth and development of children under five. A quasi-experimental design with a non-equivalent control group design was used. The intervention group used the application for 2 months, while the control group received routine services from health center. Sampling was conducted using a simple random sampling technique, involving 70 parents in each group. Data analysis used the Mann Whitney test to evaluate significant differences between the two groups. The study was conducted in Tanjungpinang City from July to October 2024. The results showed that the intervention group experienced a much greater increase in parental participation compared to the control group, with a 20% improvement and p-value <0.05. The use of the application was proven enhancing parental participation in stimulating children under five growth and development.